O Medo do Desconhecido: Uma Análise Comparada entre “The Outsider” e “The Fall Of The House Of Usher” - Pierazzo, Jaqueline (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
Edgar Allan Poe (1809-1849) and Howard Phillips Lovecraft (1890-1937) can be regarded as two of the greatest writers of terror or horror fiction. If, on the one hand, both authors left a considerable variety of fictional texts within the scope of the literature of terror, on the other hand, they were also responsible for establishing an essential theoretical basis for its consolidation and study. In a similar way, Poe’s influence on the Rhode Island writer can be divided into two scopes: fiction writings and aesthetic theory. Considering Lovecraft’s fiction, “The Outsider” is one of the tales in which Poe’s influence appears more clearly and diversely. In this tale, Lovecraft establishes a dialogue with various works by Edgar Allan Poe, especially with the stories of the so-called Dark Ladies - Berenice, Morella and Ligeia -, “William Wilson” and “The Masque of the Red Death.” However, it is his approach to “The Fall of the House of Usher” that draws the most attention. In this sense, starting from the consideration of Poe’s influence in Lovecraft, the main goal of this article is to propose a comparative reading of the stories “The Fall of the House of Usher” and “The Outsider”, based on the consideration of the points of contact and particularities of the terror of each of the writers.